ADSORPTION AND PERMEABILITY OF CLAYS PERMEATED WITH FERROUS IRON AND MANGANESE - Tufekci, Nese; Ozcoban, Mehmet Sukru; Yalcin, Sibel; Asci, Yeliz; Akguner, Cem (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2010)
In this study, the effects of inorganic permeants on the permeability of compacted clay soil have been investigated by chemical, physicochemical and sieve analyses as well as scanning electron microscopy (SEM) of the clay soil used in the experiments. Standard and modified Proctor compaction tests were applied to the clay soil obtained from the Sile-Komurcuoda Landfill Area. The effects of inorganic permeants (ferrous Iron and manganese) on the permeability of compacted clay soil samples have been analyzed. Ferrous iron and manganese have been also measured in the Influent and effluent in order to determine the treatment capability of the compacted clay soil. Adsorption of clay soil was studied in both a batch and continuous reactor. Ferrous iron and manganese have no effects on the permeability values of soils. In continuous reactor. removal efficiencies of ferrous iron in clay soil were found to be 80% for standard compaction and 96% for modified compaction whereas those of manganese in clay soil were found to be 79% for standard compaction and 90% for modified compaction In batch reactor, optimum adsorption time of ferrous iron and manganese was 2 hours
Keywords: Permeability; leachate; compacted clay soil; removal efficiency; REMOVAL RATE; TRANSPORT; Environmental Sciences & Ecology